2014
DOI: 10.1186/1471-2407-14-191
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of ezrin and phosphorylated ezrin expression in non-small cell lung cancer

Abstract: BackgroundThe cytoskeletal organizer ezrin is a member of the ezrin-radixin-moesin (ERM) family and plays important roles in not only cell motility, cell adhesion, and apoptosis, but also in various cell signaling pathways. Phosphorylation at Thr-567 and Tyr-353 are key regulatory events in the transition of the dormant to active form of ezrin. This study investigated the prognostic implications of ezrin and phosphorylated ezrin (p-ezrin) expression in non-small cell lung carcinoma (NSCLC).MethodsEzrin and p-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 30 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…In addition, it was also found that adenovirus-mediated siRNA targetting ezrin inhibits the proliferation, migration, and invasion of MG-63 cells, impedes cell cycle progression and induces apoptosis of MG-63 cells. As a cross-linker between the plasma membrane and actin cytoskeleton, ezrin participated in cell motility, membrane trafficking, as well as cell adhesion and apoptosis [ 29 ]. Bulut et al [ 30 ] demonstrated that ezrin can inhibit invasion by small molecule inhibitors to osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was also found that adenovirus-mediated siRNA targetting ezrin inhibits the proliferation, migration, and invasion of MG-63 cells, impedes cell cycle progression and induces apoptosis of MG-63 cells. As a cross-linker between the plasma membrane and actin cytoskeleton, ezrin participated in cell motility, membrane trafficking, as well as cell adhesion and apoptosis [ 29 ]. Bulut et al [ 30 ] demonstrated that ezrin can inhibit invasion by small molecule inhibitors to osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the levels of AJAP1 mRNA correlated significantly with those of EZR in ESCC and FHs74 cell lines. EZR is a member of the ezrin-radixin-moesin family and acts as a cross-linker between the plasma membrane and the actin cytoskeleton (34). Inactive EZR is located in the cytoplasm, and its C-terminal domain, an F-actin-binding site, is masked by the EZR N-terminal domain or those of other ERM proteins (35).…”
Section: Discussionmentioning
confidence: 99%
“…Despite progress in the multimodality treatment of lung cancer, prognosis is still poor, with 10-15% 5-year survival rates. More than 90% of deaths from NSCLC are attributable to metastases [ 1 , 4 ].…”
Section: Introductionmentioning
confidence: 99%